2021
DOI: 10.1038/s41398-021-01461-0
|View full text |Cite
|
Sign up to set email alerts
|

Insula sub-regions across the psychosis spectrum: morphology and clinical correlates

Abstract: The insula is a heterogeneous cortical region, comprised of three cytoarchitecturally distinct sub-regions (agranular, dysgranular, and granular), which traverse the anterior-posterior axis and are differentially involved in affective, cognitive, and somatosensory processing. Smaller insula volume is consistently reported in psychosis-spectrum disorders and is hypothesized to result, in part, from abnormal neurodevelopment. To better understand the regional and diagnostic specificity of insula abnormalities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 87 publications
7
9
0
1
Order By: Relevance
“…In other regions such as the insular or cingulate cortex, gray matter loss in CHR-T has also been reported to exceed that of CHR_NT [ 75 ]. The structural alterations reported in previous studies are in line with the identified regions in the current analysis, such as temporal regions [ 76 ]; frontal cortex [ 77 79 ]; thalamus [ 72 ]; insula [ 80 ]; hippocampus and caudate nucleus [ 81 , 82 ]; pallidum, putamen [ 83 ]; parahippocampus [ 83 , 84 ]; and lingual cortex [ 85 ]. White matter: There is accumulating evidence of compromised white matter function leading to abnormalities in synchronization and connectivity in patients with schizophrenia [ 86 ], the most widely used measure being fractional anisotropy (FA) assessed with diffusion tensor imaging (DTI).…”
Section: Discussionsupporting
confidence: 87%
“…In other regions such as the insular or cingulate cortex, gray matter loss in CHR-T has also been reported to exceed that of CHR_NT [ 75 ]. The structural alterations reported in previous studies are in line with the identified regions in the current analysis, such as temporal regions [ 76 ]; frontal cortex [ 77 79 ]; thalamus [ 72 ]; insula [ 80 ]; hippocampus and caudate nucleus [ 81 , 82 ]; pallidum, putamen [ 83 ]; parahippocampus [ 83 , 84 ]; and lingual cortex [ 85 ]. White matter: There is accumulating evidence of compromised white matter function leading to abnormalities in synchronization and connectivity in patients with schizophrenia [ 86 ], the most widely used measure being fractional anisotropy (FA) assessed with diffusion tensor imaging (DTI).…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, in our sample, we explored both the anterior and posterior insula, highlighting a different pattern of increased and decreased GM modification, as also reported by a recent study on SCZ (Tian et al, 2019). Interestingly, our results seem in line with a recent study suggesting a different involvement of insular subregions and a differential association of these subregions to both clinical and cognitive aspects in psychotic patients (Sheffield et al, 2021). Although the causes of this differential alteration of insular GM are not easy to draw, some possibilities may be considered in the context of the existing literature showing that anterior and posterior insula are part of different networks subserving different functions (Li et al, 2019).…”
Section: Baseline Resultssupporting
confidence: 80%
“…We showed that this is indeed the case among ABCD Hispanic/Latinx families, as youth of caregivers with a bicultural orientation exhibited significantly lower somatic complaints and depression. In terms of neural differences, youth of bicultural caregivers exhibited greater rs-fMRI activity (both fALFF and ReHo) in the left insula, potentially indicating increased metabolic rate of glucose and oxygen (64); these results are aligned with studies showing the insula is associated with somatic and depressive symptoms (65,66) and psychopathology broadly (6769). The current person-centered analyses examining youth differences across caregivers profiles likely captured robust effects across a complex range of family environmental factors.…”
Section: Discussionsupporting
confidence: 68%